Analisis Minat Baca Siswa melalui Program Gerakan Literasi Sekolah (GLS) Pasca Pandemi Covid-19 di SDN 8 Sesean - Weryanti Laen Langi' (LPPM UKI Toraja, 2022)
The purpose of this research is to understand the implementation of the School Literacy Movement (GLS) program in SDN 8 Sesean. This study employs a qualitative approach with a descriptive qualitative research design, and data analysis is conducted using the descriptive qualitative method. The research subjects are fourth-grade students who participate in the GLS program, while supporting informants are fourth-grade teachers at SDN 8 Sesean. Data collection is done through observation, interviews, and documentation. The results indicate that the GLS program has benefits in increasing students' reading interest and helping teachers determine students' reading abilities. The GLS program consists of three stages: the habituation stage, the development stage, and the learning stage. Supporting factors for the GLS program are related to facilities and infrastructure as well as reading materials. Although reading materials are still lacking, students' enthusiasm for reading is not reduced. The inhibiting factors include a lack of reading materials, a lack of students' interest in reading, teachers who have not fully followed the implementation of the GLS program, and students who do not understand the importance of reading books. The keywords for this study are School Literacy Movement program and students' reading interest.